Mild head injury with isolated third nerve palsy. Issue 4 (1st July 2001) - Muthu, P; Pritty, P
Abstract : Traumatic isolated cranial nerve palsies are uncommon and when they do occur, they are usually associated with severe head trauma. Cranial nerve palsy associated with mild head injury is rare. A case is reported of complete left third nerve palsy associated with mild head injury. The rate of recovery for complete third nerve palsy is slow and prolonged. The ptosis recovered in 10 months; the divergent squint required botulinum toxin to the lateral rectus muscle followed by surgery.